Process Innovation Tools and Strategies in Production Management - Erdei, Edina (International Journal of Engineering and Management Sciences, 2018)
The method of process innovation helps to recognize the opportunities in production processes that represent clear competitive advantage. Using it, up to 30% change is available in increasing productivity and in the reducing of costs, stocks, and lead times. There is no need for complicated methods in the process development. The power of logical, simple tools relies on the fact that everyone can learn, understand, apply them and give quick feedback about their operation. Significant changes have been made in today's possibilities of designing and operating production systems. The emergence of cyber physical systems, the opportunities offered by big data, and the "Internet of Things" (Internet of Things) have shown strong research potential for more efficient logistics and manufacturing systems. The potential of network co-operation, information gathered from tracing materials in production and communication between machines provide a wide-range of optimization opportunities for manufacturing processes. The toolkit presented in the research cannot only be used in direct production; almost all parts of the value creation process can be broken down into routine actions, so the causes of the problems can be analyzed and the development of the process’ parts can be easier implemented.